2022
DOI: 10.1002/1878-0261.13190
|View full text |Cite
|
Sign up to set email alerts
|

Integrating bulk and single‐cell RNA sequencing reveals cellular heterogeneity and immune infiltration in hepatocellular carcinoma

Abstract: Efficacy of immunotherapy in hepatocellular carcinoma (HCC) is blocked by its high degree of inter‐ and intra‐tumor heterogeneity and immunosuppressive tumor microenvironment. However, the correlation between tumor heterogeneity and immunosuppressive microenvironment in HCC has not been well addressed. Here, we endeavored to dissect inter‐ and intra‐tumor heterogeneity in HCC and uncover how they contribute to the immunosuppressive microenvironment. We performed consensus molecular subtyping with non‐negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 43 publications
(52 reference statements)
0
23
0
Order By: Relevance
“…Negative regulation of immune checkpoint molecules was one of the major factors leading to the exhaustion or dysfunction of effector memory CD8+ T cell, and late exhausted or dysfunctional T cells, representing impaired proliferation ability and reduced production of cytokines, further led to a weakened anti-tumor response ( 61 ). High expression levels of TIGIT and PDCD1 were recognized as immunosuppressed tumors with the poorest prognosis ( 62 ). Meanwhile, we further predicted the response to immunotherapy in high- and low-risk groups of HCC patients using IPS, with patients in the low-risk group associated with increased immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Negative regulation of immune checkpoint molecules was one of the major factors leading to the exhaustion or dysfunction of effector memory CD8+ T cell, and late exhausted or dysfunctional T cells, representing impaired proliferation ability and reduced production of cytokines, further led to a weakened anti-tumor response ( 61 ). High expression levels of TIGIT and PDCD1 were recognized as immunosuppressed tumors with the poorest prognosis ( 62 ). Meanwhile, we further predicted the response to immunotherapy in high- and low-risk groups of HCC patients using IPS, with patients in the low-risk group associated with increased immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular subtypes may be associated with different aetiologies, survival outcomes and immune responses 99,100,102–104 . Immune classifications have largely been based on inference of immune cell subsets from transcriptome data in HCC TME 31,105–108 . Thorsson et al identified six general cancer immune subtypes spanning several cancer entities in The Cancer Genome Atlas (TCGA) study.…”
Section: The Heterogeneity Of the Hcc Tumour Immune Microenvironmentmentioning
confidence: 99%
“…The presence of T cells as well as cytotoxic T cells, the active immune response and CD45‐high but FoxP3‐low tumours were individually related to prolonged OS 30,31,107 . In contrast, the expression of immunosuppressive or exhausted features of infiltrating immune cells dominates the immune‐exhausted subclass that was associated with poorer prognosis among all immune subtypes 31,105,107 . It is characterized by signatures of immunosuppressive or exhausted cell populations such as Tregs, Th17 cells, regulatory B cells (Bregs), tumour‐associated macrophages (TAMs) and TEX, higher expression of immunoregulatory molecules (e.g., VEGFA, CTLA4, TIM‐3 and TIGIT) and is associated with intratumour steatosis (Figure 2).…”
Section: The Heterogeneity Of the Hcc Tumour Immune Microenvironmentmentioning
confidence: 99%
See 2 more Smart Citations